Correlation between the topologically close-packed structure and the deformation behavior of metallic Cu64.5Zr35.5. Issue 45 (16th November 2021) - Zhou, Li-Li; Tian, Ze-An; Liang, Yong-Chao; Mo, Yun-Fei; Wang, Cun-Jing; Li, Fang-Zuo
Abstract : The deformation response of the largest standard clusters depends both on the nearest characteristics and the linking pattern between them. Abstract : The topologically close-packed (TCP) structural characteristics in a model metallic glass (MG) of Cu64.5 Zr35.5 have been investigated by molecular dynamics simulations. A group of structural indicators based on the largest standard cluster (LaSC) have been correlated with the non-affine displacement ( D 2 ) of atoms, so as to reveal the hidden correlation between local structures and deformation behavior of Cu64.5 Zr35.5 during compression. It was found that the 15 types of Top-10 LaSCs are all TCP-like ones, among which the most numerous icosahedron (Z12 and 1-Z12) decreases in population sharply and moderately during respectively the elastic and yield region of compression; while in the fluid-flow region, the number of all Top-10 LaSCs tends to be almost constant. Low- D 2 atoms prefer to link with each other; while medium- D 2 atoms act as transition structures between backbone areas and deformation areas. Most interestingly, the deformation response of TCP-like atoms is not only determined by its nearest neighbor characteristics, but also depends on the linkage with other atoms. In addition, icosahedral atoms with a higher degree of medium range five-fold symmetry (MRFFS) are more resistant to the stress-induced deformation. Therefore, the TCP characteristics, including its nearest neighbor feature and the inter-connection between TCP LaSCs, are closely related with the deformation behavior of atoms, especially the MRFFS (up to 5 layers) of icosahedral atoms. These findings shed new light on the understanding of the relationship between microstructure and deformation response of MGs, which will promote the development of deformation theory of MGs.